2019
DOI: 10.1111/jam.14207
|View full text |Cite
|
Sign up to set email alerts
|

Alicycliphilus : current knowledge and potential for bioremediation of xenobiotics

Abstract: Summary Alicycliphilus is a promising candidate for participating in the development of novel xenobiotics bioremediation processes. Members of the Alicycliphilus genus are environmental bacteria mostly found in polluted sites such as landfills and contaminated watercourses, and in sewage sludges from wastewater treatment plants. They exhibit a versatile metabolism and the ability to use oxygen, nitrate and chlorate as terminal electron acceptors, which allow them to biodegrade xenobiotics under oxic or anoxic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(16 citation statements)
references
References 68 publications
(178 reference statements)
1
15
0
Order By: Relevance
“…Biodegradation of acetone with Alicycliphilus sp. is carried out by carboxylation of acetone to acetoacetate, catalyzed by acetone carboxylase, activation to acetoacetyl-CoA and cleaving into two acetyl-CoA molecules [ 68 ]. Treatment with activated carbon removes compounds by physical adsorption onto activated carbon (AC) bed, which needs to be replaced/regenerated after some time.…”
Section: Methodsmentioning
confidence: 99%
“…Biodegradation of acetone with Alicycliphilus sp. is carried out by carboxylation of acetone to acetoacetate, catalyzed by acetone carboxylase, activation to acetoacetyl-CoA and cleaving into two acetyl-CoA molecules [ 68 ]. Treatment with activated carbon removes compounds by physical adsorption onto activated carbon (AC) bed, which needs to be replaced/regenerated after some time.…”
Section: Methodsmentioning
confidence: 99%
“…The bacterial genus can potentially help in the bioremediation of different antibiotic classes. One of the studies by [192] showed the degradation of TC and OTC by Alicycliphilus [192]. A. denitrificans were reported to remove the TET up to 95% [201] and its analog OTC up to 70% [36].…”
Section: Remediation and Ecological Resiliencementioning
confidence: 99%
“…The cluster analysis results showed that Bands 1, 2, 3, and 4 were Alicycliphilus denitrificans K601, Alicycliphilus sp. R-2461 hits, Uncultured Alicycliphilus sp., and Acidovorax aerodenitrificans hits, respectively, among which Alicycliphilus denitrificans K601 strains have been reported to degrade phenol, benzene, and toluene [10,42]. Alicycliphilus denitrificans K601 is a short rod-shaped aerobic gram-negative bacterium that can grow on aerobic sewage sludge.…”
Section: Microorganismmentioning
confidence: 99%